Practice of contraceptives - pandey, S.; KARKI, S.; Pradhan, A. (Journal of Institute of Medicine Nepal, 2009)
Introduction: Over the past decades fertility rate have surprisingly been stagnated demanding further research on the ways it reduces rate to a level appropriate for healthy population. Considering the status of male in developing countries like Nepal, it is believed that men play vital role in achieving success in this sector. Therefore this study was done to find out the knowledge and practice of contraceptives among married males of Makwanpur, Nepal. Methods: This is a cross-sectional descriptive study. Data were collected from the 387 respondents by personal interview using semi-structured questionnaire. Results: Mean age of the respondents was 34.48 years. Most of the respondents knew at least four contraceptive methods. There is a strong relationship between knowledge and the use of contraceptives with the level of education and economic status having a direct impact. The attitude of male respondents to share responsibility for promotion of contraceptive was found to be positive. Conclusions: Almost majority agree that the responsibility for contraception should shared by both partner, but use of contraceptive methods among men is still low. This study recommended in depth action research to promote male contraceptive methods and priority for service delivery program in Nepal.